Endosperm structure and Glycemic Index of Japonica Italian rice varieties - Haxhari, Filip; Savorani, Francesco; Rondanelli, Mariangela; Cantaluppi, Enrico; Campanini, Luigi; Magnani, Edoardo; Simonelli, Cinzia; Gavoci, Gentian; Chiadò, Alessandro; Sozzi, Mattia; Cavallini, Nicola; Chiodoni, Angelica; et al. (Frontiers in Plant Science, 2024)
Introduction Given that rice serves as a crucial staple food for a significant portion of the global population and with the increasing number of individuals being diagnosed with diabetes, a primary objective in genetic improvement is to identify and cultivate low Glycemic Index (GI) varieties. This must be done while ensuring the preservation of grain quality. Methods 25 Italian rice genotypes were characterized calculating their GI “in vivo” and, together with other 29 Italian and non-Italian genotypes they were studied to evaluate the grain inner structure through Field Emission Scanning Electron Microscopy (FESEM) technique. Using an ad-hoc developed algorithm, morphological features were extracted from the FESEM images, to be then inspected by means of multivariate data analysis methods. Results and Discussion Large variability was observed in GI values (49 to 92 with respect to glucose), as well as in endosperm morphological features. According to the percentage of porosity is possible to distinguish approximately among rice varieties having a crystalline grain (< 1.7%), those intended for the preparation of risotto (> 5%), and a third group having intermediate characteristics. Waxy rice varieties were not united by a certain porosity level, but they shared a low starch granules eccentricity. With reference to morphological features, rice varieties with low GI (<55) seem to be characterized by large starch granules and low porosity values. Our data testify the wide variability of Italian rice cultivation giving interesting information for future breeding programs, finding that the structure of the endosperm can be regarded as a specific characteristic of each variety.